THE MORPHOLOGY OF HETEROGENEITY OF SEEDS OF VEGETABLE UMBELLIFERAE CROPS CAUSED BY PLACE OF DEVELOPMENT ON THE PARENTAL PLANT - A. F. Buharov; D. N. Baleev (Овощи России)
Study of morphological parameters of seeds is of interest for the enhancement of quality of produced seeds vegetable Umbelliferae plants. Indicators of the linear dimensions of the embryo, endosperm, seed, and the degree of variability can be used for additional performance of a lot of seeds. Knowledge of morphology of heterogeneity of seeds should be taken into account in their growing, sorting, storage and presowing refinement.